Solve problems with branching algorithms using Scratch software - Siddikov Ilhomjon Meliqozievich; Abdurashidova Sevara Iqboljon qizi (Zien Journals, 2022)
This article provides information about the importance of Scratch in education, the creation of animation and interactive projects, cartoons and other multimedia products in the Scratch programming environment, the convenience, interface and capabilities of the Scratch working environment for students of all ages.
Keywords: Scratch; animation; interface; events